2019
DOI: 10.1111/bjh.15960
|View full text |Cite
|
Sign up to set email alerts
|

Early T precursor acute lymphoblastic leukaemia/lymphoma shows differential immunophenotypic characteristics including frequent CD33 expression and in vitro response to targeted CD33 therapy

Abstract: Summary The differential immunophenotypic characteristics of early T precursor (ETP) acute lymphoblastic leukaemia/lymphoma (ALL) remain incompletely characterized. The study group (n = 142) included 106 (74·7%) men and 36 (25·3%) women with a median age of 34·9 years (range, 2–79) at diagnosis. Patients were subtyped by flow cytometry immunophenotyping as follows: 33 (23·2%) ETP; 32 (22·5%) early non‐ETP; 60 (42·2%) thymic; and 17 (12·1%) mature. Excepting definitional markers, there was a significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 28 publications
6
27
1
Order By: Relevance
“…18 Scoring schemas based on immunophenotypic profiles have been reported in an attempt to distinguish ETP-ALL from other leukemias. 7,9,19 Notably, it may be challenging to distinguish ETP-ALL from mixed phenotype acute leukemia. 6 ETP-ALL is uncommon (reports of ETP range from 5% to 36% in T cell ALL series/studies).…”
Section: Etp-all: a Distinct Entity Of T-cell Allmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Scoring schemas based on immunophenotypic profiles have been reported in an attempt to distinguish ETP-ALL from other leukemias. 7,9,19 Notably, it may be challenging to distinguish ETP-ALL from mixed phenotype acute leukemia. 6 ETP-ALL is uncommon (reports of ETP range from 5% to 36% in T cell ALL series/studies).…”
Section: Etp-all: a Distinct Entity Of T-cell Allmentioning
confidence: 99%
“…The CD33 and CD123 may be positive and appear to be so more frequently compared with non-ETP-ALL. 8,9 Interestingly, ETP-ALL with co-expression of B-cell markers has been reported, but the numbers of patients were small. 10 The clinical significance of B-cell marker expression is unclear.…”
Section: Etp-all: a Distinct Entity Of T-cell Allmentioning
confidence: 99%
“…Angelova and colleagues detected CD123 expression in 43.3% of T-ALL, with the vast majority of cases (92.3%) having early T precursor (ETP) or early non-ETP immunophenotype [23(Khogeer, 2019 #136)(Jain, 2016 #134)] [ 53 , 54 ]. Notably, their findings, in line with those reported by others [ 2 ], indicated that CD123 expression on leukemic cells in T-ALL was at a lower MFI compared to B-ALL.…”
Section: Cd123 Expression In Hematologic Malignanciesmentioning
confidence: 99%
“…As one of the routine examinations, the expression of relevant cell surface markers was measured by the flow cytometry [7]. However, the diagnosis can be varied depending on different pathologists and/or different parameters, for instance, the voltage setting.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnosis can be varied depending on different pathologists and/or different parameters, for instance, the voltage setting. In order to improve the reliability of the diagnosis, Khogeer et al developed a scoring system based on 11 surface markers to re-define the ETP subgroup [7]. Still, it is solely based on the measurement a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 of flow cytometry.…”
Section: Introductionmentioning
confidence: 99%